“HUMAN ENOUGH TO PERSUADE?” A SYSTEMATIC REVIEW OF VIRTUAL INFLUENCER AUTHENTICITY AND PARASOCIAL ATTACHMENT - Shahnaz Khumaira (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study aims to synthesize and map the development of research on virtual influencers by focusing on authenticity, parasocial relationships, and consumer behavioral responses. The background of this study arises from the growing use of virtual influencers in digital marketing and the need to understand their effectiveness compared to human influencers. The objective of this research is to identify key findings across existing studies using a Systematic Literature Review (SLR) guided by the PRISMA 2020 protocol. Literature searches were conducted across four major databases—Scopus, ScienceDirect, Emerald Insight, and Google Scholar—resulting in 107 articles. After title and abstract screening, duplicate removal, and full-text assessment, 30 articles met the inclusion criteria. The findings indicate that virtual influencer authenticity is constructed through persona consistency, narrative cues, and human-likeness. Parasocial relationships serve as a central psychological mechanism that mediates the influence of virtual influencers on trust, emotional engagement, and purchase intention. Consumer responses are strongly affected by credibility and identity congruence with the virtual influencer. In conclusion, the effectiveness of virtual influencers is shaped by a combination of narrative and psychological factors, and these insights provide a strong theoretical foundation for future research.